The evolution of robotic thoracic surgery - Zirafa, Carmelina C. (Ann Cardiothorac Surg, 2019)
Robotic surgery has the features to represent the future of surgery, considering the rapid evolution of its technology and the resulting in the surgical field. In the last years, the robotic technique in thoracic surgery has progressively become widespread in the word, particularly for the treatment of the mediastinal and pulmonary lesions. The development of technology in the robotic system has been associated with the improvement of intraoperative and postoperative results. Due to the satisfying results and increasing experience and confidence with the robotic technique, surgeons are consequently enlarging the surgical indication, moving to increasingly challenging cases. Thoracic robotic surgery is being affirmed as a safe technique also for those complex cases, which in the past were considered a matter solely for open surgery. In fact, robotic surgery is increasingly associated with positive surgical results and guarantees less traumatism and a fast recovery to the patients. These positive results have resulted from the evolution of the technique, which has developed in parallel with the evolution of the technology, exploiting to its best the latest features of the robotic system. These features, such as the fluorescence-detection tool or the robotic stapler, have been aiding the surgeon to maximise the safety and feasibility of the application of the robotic technique to thoracic surgery.